PENGARUH PENGGUNAAN CELEBRITY ENDORSER KOMENG PADA NIAT BELI KONSUMEN (STUDI KASUS PENGGUNA SHOPEE GEN Z DI BANDAR LAMPUNG) - Efendi, Nandar; Septiani, Monica; Candra, Ade (Journals of Economics and Business, 2024)
A celebrity endorser is someone who is famous and uses public recognition to recommend or present products in advertisements to attract consumers' attention. Currently, many companies use the services of celebrity endorsers to promote their products or services to influence consumers purchasing intentions. Consumer intentions are used to predict future consumer behavior. The method used in the research is quantitative using 100 respondents from the people of Bandar Lampung City who are Gen Z and have used Shopee services. The SPSS 25.0 application was used in data analysis techniques by testing multiple linear regression and t-tests, to see the influence of celebrity endorsers on the purchasing intentions of Gen Z consumers. The partial research results show that celebrity endorsements influence the purchasing intentions of Gen Z consumers quite significantly. The influence of using celebrity endorser services can be seen from three dimensions, namely attractiveness, expertise, and trustworthiness. The celebrity endorser variable, the trustworthiness dimension, has a positive, but not significant, influence on consumer purchase intentions. Meanwhile, the dimensions of attractiveness and expertise have a positive and significant influence on consumer purchasing intentions, especially Gen-Z in Bandar Lampung City. The results of this research show that a celebrity endorser has a significant influence in advertising the products that clients want. This research has several limitations in the use of variables, so further research can add other variables to measure the effect of using celebrity endorsers on consumer purchase intentions.Keywords: Celebrity Endorser, Purchase Intention, Gen Z,